2022
DOI: 10.1093/nar/gkac493
|View full text |Cite
|
Sign up to set email alerts
|

HSFs drive transcription of distinct genes and enhancers during oxidative stress and heat shock

Abstract: Reprogramming of transcription is critical for the survival under cellular stress. Heat shock has provided an excellent model to investigate nascent transcription in stressed cells, but the molecular mechanisms orchestrating RNA synthesis during other types of stress are unknown. We utilized PRO-seq and ChIP-seq to study how Heat Shock Factors, HSF1 and HSF2, coordinate transcription at genes and enhancers upon oxidative stress and heat shock. We show that pause-release of RNA polymerase II (Pol II) is a unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…Mapped reads were processed from bed files to coverage files, retaining only the 3′ end nucleotide (active sites of transcription) of each read. Density normalized bedgraph files were adjusted by sample-specific normalization factors as described previously (Booth et al, 2018; Himanen et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Mapped reads were processed from bed files to coverage files, retaining only the 3′ end nucleotide (active sites of transcription) of each read. Density normalized bedgraph files were adjusted by sample-specific normalization factors as described previously (Booth et al, 2018; Himanen et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, ROS might manifest both ferroptosis meditated cell death as well as survival signals that lead to an equilibration between cell death and survival outcomes. Moreover, HSF2, a homolog of HSF1, functions in cooperation with HSF1 as the heterotrimer that binds to oxidative stress-specific target genes in response to increased ROS-mediated oxidative stress 129 . Given the recent findings that the interaction between HSF1 and HSF2 is essential for cancer gene expression 24 , 129 , an important role of HSF2 in cancer development may become increasingly significant.…”
Section: Hsf1 Regulates Several Cancer-related Cellular Functionsmentioning
confidence: 99%
“…The first session of the meeting was focused on Cellular Stress Responses, starting with Lea Sistonen (Åbo Akademi University, Turku, Finland) who summarized the results of their recently published work on the stress-type specific transcriptional programs driven by the Heat Shock Factors 1 and 2 (HSF1 and HSF2) (Himanen et al 2022 ). The Sistonen lab found that in human cells of epithelial origin, HSF2 is strongly suppressed by TGF-β, which results in destabilized cell–cell adhesion contacts and increased cellular motility.…”
Section: Cellular Stress Responsesmentioning
confidence: 99%